PENANAMAN BIBIT BUAH UNTUK MEWUJUDKAN GREEN LIFESTYLE FOR HEALTHY LIVING DI MASYARAKAT KABUPATEN JEMBER: Penanaman Bibit Buah Untuk Mewujudkan Green Lifestyle For Healthy Living Di Masyarakat Kabupaten Jember - Imam Muslim; Diah Sudiarti; Teguh Karya Pamungkas (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
Ecosystem degradation and increasing dependence on fruit supplies from outside the region have become significant environmental and public health challenges in Jember Regency. Land-use conversion, vegetation loss, and long distribution chains not only reduce environmental quality but also affect fruit quality, community health, and local economic stability. This community service activity aimed to enhance public awareness of the importance of adopting a green lifestyle for healthy living while providing practical education on sustainable fruit planting and maintenance techniques. The activity employed a participatory approach with site selection based on purposive sampling in Sukorejo Village, Bangsalsari District, Jember Regency. Participants included members of the Branch and Sub-Branch Boards of Fatayat NU Jember Regency. The program consisted of environmental socialization sessions, hands-on fruit seed planting activities, and the distribution of 2,000 fruit seedlings to participants. Data were collected through observation, interviews, and documentation and analyzed using descriptive qualitative methods. The findings indicate active participant involvement throughout all stages of the program and an increased understanding of the ecological, health, and food security benefits of fruit tree cultivation. Moreover, participants demonstrated the potential to act as agents of change by disseminating green lifestyle practices within their communities. The implications of this activity suggest that participatory fruit planting initiatives can serve as an effective strategy to strengthen environmental awareness, promote healthier living conditions, and support sustainable local economic empowerment through community-based food independence.